Characterization of brake particles emitted from non-asbestos organic and low-metallic brake pads under normal and harsh braking conditions. (1st June 2022) - Woo, Sang-Hee; Jang, Hyungjoon; Na, Min Young; Chang, Hye Jung; Lee, Seokhwan
Abstract: The physicochemical characteristics of micro- and nano-sized brake particles emitted from non-asbestos organic (NAO) and low-metallic (LM) brake pads were investigated under normal and harsh braking conditions using a brake dynamometer. Under normal braking conditions, 28% and 12% of the total wear mass of brake pad and disc was emitted as PM10 and PM2.5, respectively. Overall, the LM pad emitted 4 times higher brake wear PM than the NAO pad. There was no difference in the morphology of brake wear particles (BWPs) according to pad type from the two pad types. BWPs emitted from the NAO pad were mainly composed of Fe oxide and potassium hexatitanate particles, whereas BWPs from the LM pad were almost entirely of Fe oxide particles. Even when the critical pad temperature was not reached, nanoparticles 80–200 nm in size were emitted from both pad types, and the emission concentration of the LM pad was 3–4 times higher than that of the NAO pad. When the pad temperature exceeded the critical temperature by repeated harsh braking, high particle number (PN) concentrations of volatile nanoparticles were measured. Brake nanoparticles 10–50 nm in size formed out of 10 nm sized particles through volatilization and nucleation. Notably, the PN concentration of volatile NAO pad nanoparticles was 3–4 times higher than that of LM pad nanoparticles due to a higher organic fraction in NAO pads. Volatile nanoparticles smaller than 50 nm could be efficiently removed using volatile particle removers such as an evaporation tube and a catalytic stripper, and the evaporation tube had a higher removal efficiency of volatile nanoparticle than the catalytic stripper. Scanning transmission electron microscopy and energy dispersive spectroscopy analysis showed that nanoparticles of size around 50 nm were round and adhered to larger particles. Graphical abstract: Image 1 Highlights: Brake particles emitted from NAO and LM pad were characterized. The micro- and nano-sized particles under normal and harsh braking were investigated. The morphology and chemical components of particles were analyzed using SEM and TEM. The efficiency of volatile particle removers for brake nanoparticles was determined.